Effects of the initial stress and spalling strength on spalling around deposition holes and tunnels. Issue 1 (1st January 2023) - Figueiredo, B; Vatcher, J; Sjöberg, J; Ivars, D Mas
Abstract: Spalling in the deposition holes and tunnel stability are of concern for the design of deep geological repositories for spent nuclear fuel. A 3D numerical stress model, including a single deposition tunnel and multiple deposition holes to analyse the potential for spalling resulting from the excavation phase, was developed for the proposed repository location at the Forsmark site. Several potential initial stress field cases and spalling strengths of the intact rock were considered. The magnitudes of the factor of safety, the spalling depth, the minor principal stress, and the differential stress were evaluated. The results showed that no spalling in the central deposition hole is indicated for the most likely stress field, and the occurrence of spalling and the spalling depth are minimised for a maximum horizontal stress aligned approximately parallel to the tunnel axis. For spalling occurrence and depth of spalling, the magnitude of the maximum horizontal stress is more critical than its orientation, and the spalling strength is more critical than the magnitude of the maximum horizontal stress. No instability problems were indicated in the vicinity of the roof for all analysed stress cases.